Women Empowerment: Key to Socio-Economic Development - Saima Khan (International Journal on Women Empowerment, 2018)
Background: Empowering a women is the key issue in developing nations. Despite of the fact that women are an integral part of any society, yet their involvement in decision making via their active contribution in economic activities is very low. Women empowerment and economic development are interlinked, where on one hand, development alone can play a major role in driving down inequality between women and men while on the other hand, empowering women can benefit development. Methodology: A short communication of 5 years i.e. 2014-2018. Databases used were Google Scholar, PubMed, Research gate, Scopus and web of science. Results: Providing consideration of working at individual consciousness level in order to develop women's sense of their own potentials and critical recognitions of the obstacles within social dimensions, so that women identifies their potentials and put efforts together with other women like a distinctive power to confront inequalities and injustice, will turn out to be ‘power for’ positive societal modifications. Also setting resources in hands of underprivileged women while discouraging gender inequality not only at home but also in society results in enormous development settlements. Those Expanding opportunities for women’s in communal works, investment, agricultural and further areas hasten economic progression, helping to lessen the effects of current and future financial crises. Conclusion: For improving quality of life there is high necessity of fundamental alterations. Policies should be created to improve the women status as useful society members. There is a high necessity of women’s active participation not only in decision making processes but also in planning and implementation of development programs.